FAKTOR RISIKO DERMATITIS KONTAK AKIBAT KERJA PADA PEKERJA INDUSTRI TEPUNG PATI AREN TRADISIONAL DI DESA TULUNG KLATEN - , Ratih Pramuningtyas ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Occupational contact dermatitis is an inflammatory reaction caused by exposure to occupational factors. Contact dermatitis due to plants or plant products are often found in clinical practice. Occupational contact dermatitis was common in traditional starch industry worker and palm sugar was the main ingredient of this industry. Palm sugar or Arenga pinnata Merr contain ingredients that potentially irritant and allergenic. Frequency and risk factors that affected the frequency of occupational contact dermatitis in traditional starch industry worker is unknown. Objective: To determine frequency and risk factors that affected the frequency of occupational contact dermatitis in traditional starch industry worker Methods: Analytic observational study with a cross-sectional design Results: Sixty nine subjects were include in this study, 82.6% are women. The mean age of subjects was 43.3 years old. Frequency of OCD on starch industral worker was 18.8%. In bivariate analysis, wet work (p=0,043) and history of atopy (p <0.05, RP 25,3(4.87 to 132.34)) was significantly associated with the incidence of occupational contact dermatitis. Contact dermatitis which appears on the subject was irritation, caused by palm sugar and water. Patch test results show that ethanol extract of Arenga pinnata Merr has an irritant effect. Conclusion: The frequency of occupational contact dermatitis was 18.8% and There is a significant association between wet work and history of atopy with occupational contact dermatitis among traditional starch industry workers